Improving Undergraduates’ and Postgraduates’ Academic Writing Skills with Strategy Training and Feedback - Wischgoll, Anke (Frontiers in Education, 2017)
To improve text quality in higher education, training writing strategies (i.e., text structure application, summarization, or language use) and provision of feedback for revising (i.e., informative tutoring feedback or try-again feedback) were tested in combination. The aim was to establish whether first, strategy training affects academic writing skills which promote coherence, second, whether undergraduates and postgraduates benefit differently from feedback for revising, and third, whether training text structure application strategy in combination with informative tutoring feedback was most effective for undergraduates’ text quality. Undergraduate and postgraduate students (N=212) participated in the two-hour experimental intervention study in a computer-based learning environment. Participants were divided into three groups and supported by a writing strategy training intervention (i.e., text structure knowledge application, summarization, or language use) which was modelled by a peer-student in a learning journal. Afterwards participants wrote an abstract of an empirical article. Half of each group received in a computer-based learning environment twice either try-again feedback or informative tutoring feedback while revising their drafts. Writing skills and text quality were assessed by items and ratings. Analyses of co-variance revealed that, first, text structure knowledge application strategy affected academic writing skills positively; second, feedback related to writing experience resulted in higher text quality: undergraduates benefitted from informative tutoring feedback, postgraduates from try-again feedback; and third, the combination of writing strategy and feedback was not significantly related to improved text quality.